FOODBORNE PARASITES IN COLOMBIA - Jorge Enrique Gomez-Marin (Asociación Colombiana de Infectología, 2018)
This number of Infectio includes the first report of Anisakis in edible fish in the Colombian pacific coast. Anisakidiasis has become an increasing threat given the extensive consumption of Sushi and raw fish worldwide as consequence of a global fad food. This report of Anisakis in 42% of the most popular fish specimens consumed in the country, call the attention also about the new health risks present in food, particularly parasites. The Food and Agriculture Organization of the United Nations (FAO) and the World Health Organization (WHO) established a ranking of the top foodborne parasites for control priority in 2014